Global DEM derivatives at 250 m, 1 km and 2 km based on the MERIT DEM - Tomislav Hengl (Zenodo, 2018)
Layers include: various DEM derivatives computed using SAGA GIS at 250 m and using MERIT DEM (Yamazaki et al., 2017) as input. Antartica is not included. MERIT DEM was first reprojected to 6 global tiles based on the Equi7 grid system (Bauer-Marschallinger et al. 2014) and then these were used to derive all DEM derivatives. To access original DEM tiles please refer to MERIT DEM download page . To access and visualize maps use: OpenLandMap.org If you discover a bug, artifact or inconsistency in the maps, or if you have a question please use some of the following channels: Technical issues and questions about the code: https://gitlab.com/openlandmap/global-layers/issues General questions and comments: https://disqus.com/home/forums/landgis/ All files internally compressed using "COMPRESS=DEFLATE" creationoption in GDAL. File naming convention: dtm = theme: digital terrain models, twi = variable: SAGA GIS Topographic Wetness Index, merit.dem = determination method: MERIT DEM, m = mean value, 1km = spatial resolution / block support: 1 km, s0.0cm = vertical reference: land surface, 2017 = time reference: year 2017, v1.0 = version number: 1.0